1999
DOI: 10.1074/jbc.274.46.32869
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity Labeling of Wild-type and Mutant Forms of the Yeast V-ATPase A Subunit by 2-Azido-[32P]ADP

Abstract: To test the proximity of these aromatic residues to the adenine ring, the yeast V-ATPase containing wild-type and mutant forms of the A subunit was reacted with 2-azido-[ 32 P]ADP, a photoaffinity analog that stably modifies tyrosine but not phenylalanine residues. Mutant forms of the A subunit were constructed in which the two endogenous tyrosine residues were replaced with phenylalanine and in which a single tyrosine was introduced at each of the four positions. Strong ATP-protectable labeling of the A subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Therefore the in vivo V 1 re-distribution that was induced by salicylihalamide cannot be explained by a simple pH effect alone. Although the salicylihalamide effect in vivo is consistent with previous observation that inhibition of V-ATPase activity in yeast through mutagenesis blocks dissociation (19,34), the correlation between the activity of V-ATPase and its reversible dissociation has not been clearly established. Mutagenesis studies with subunit D showed that a mutant with only 6% of wild-type level of proton pumping activity still demonstrated normal dissociation in response to glucose deprivation (35), whereas some mutations in subunit A resulted in a partial or complete blocking of dissociation despite possessing more than 30% of wild-type levels of activity (25).…”
Section: Discussionsupporting
confidence: 71%
“…Therefore the in vivo V 1 re-distribution that was induced by salicylihalamide cannot be explained by a simple pH effect alone. Although the salicylihalamide effect in vivo is consistent with previous observation that inhibition of V-ATPase activity in yeast through mutagenesis blocks dissociation (19,34), the correlation between the activity of V-ATPase and its reversible dissociation has not been clearly established. Mutagenesis studies with subunit D showed that a mutant with only 6% of wild-type level of proton pumping activity still demonstrated normal dissociation in response to glucose deprivation (35), whereas some mutations in subunit A resulted in a partial or complete blocking of dissociation despite possessing more than 30% of wild-type levels of activity (25).…”
Section: Discussionsupporting
confidence: 71%
“…This absorbance effect was eliminated by measuring the decrease in NADH absorbance at 360 nm instead of 341 nm, at which wavelength interference due to absorbance of light by chloroquine is negligible. Because 80% of control activity is far in excess of what is required to allow in vivo dissociation of the V-ATPase to occur (16,58), chloroquine does not appear to block glucose-dependent dissociation of V 1 V 0 by directly inhibiting V-ATPase activity.…”
Section: Figmentioning
confidence: 99%
“…Effect of Vacuolar Neutralization on in Vivo Glucose-dependent Dissociation of the V-ATPase-In yeast, dissociation of the V 1 and V 0 domains in response to glucose depletion has been shown to require catalytic activity of the V-ATPase (16,58). Consistent with this, the R219K mutation in the nonhomologous region that inhibits Ͼ90% of both proton transport and ATPase activity in isolated vacuolar membranes results in a block in glucose-dependent dissociation (29).…”
Section: Atp Dependence Of the Coupling Efficiency Of Proton Transpormentioning
confidence: 99%
See 1 more Smart Citation
“…V 1 is composed of eight different subunits (A-H) of molecular mass 70 -13 kDa that are present in a stoichiometry of A 3 B 3 C 1 D 1 E 1 F 1 G 2 H 1-2 (14, 15) and that form a complex of ϳ640 kDa. Both the A and B subunits participate in nucleotide binding, with the catalytic sites located on the A subunits (16,17). The V 0 domain is a 240-kDa complex composed of five different subunits (a, d, c, cЈ, and cЉ) of molecular mass 100 -16 kDa that are present in a stoichiometry of a 1 d 1 c 4 c 1 Јc 1 Љ (14, 18).…”
mentioning
confidence: 99%